Biofabrication Strategies and Engineered In Vitro Systems for Vascular Mechanobiology. Issue 8 (25th February 2020) - Pradhan, Shantanu; Banda, Omar A.; Farino, Cindy J.; Sperduto, John L.; Keller, Keely A.; Taitano, Ryan; Slater, John H.
Abstract: The vascular system is integral for maintaining organ‐specific functions and homeostasis. Dysregulation in vascular architecture and function can lead to various chronic or acute disorders. Investigation of the role of the vascular system in health and disease has been accelerated through the development of tissue‐engineered constructs and microphysiological on‐chip platforms. These in vitro systems permit studies of biochemical regulation of vascular networks and parenchymal tissue and provide mechanistic insights into the biophysical and hemodynamic forces acting in organ‐specific niches. Detailed understanding of these forces and the mechanotransductory pathways involved is necessary to develop preventative and therapeutic strategies targeting the vascular system. This review describes vascular structure and function, the role of hemodynamic forces in maintaining vascular homeostasis, and measurement approaches for cell and tissue level mechanical properties influencing vascular phenomena. State‐of‐the‐art techniques for fabricating in vitro microvascular systems, with varying degrees of biological and engineering complexity, are summarized. Finally, the role of vascular mechanobiology in organ‐specific niches and pathophysiological states, and efforts to recapitulate these events using in vitro microphysiological systems, are explored. It is hoped that this review will help readers appreciate the important, but understudied, role of vascular‐parenchymal mechanotransduction in health and disease toward developing mechanotherapeutics for treatment strategies. Abstract : Dysregulation of the vascular system plays a major role in many diseases. Engineered systems designed to investigate vascular pathophysiology, development, and function are emerging. Coupled with controlled flow and pressure, these vascularized microphysiological systems enable scale‐spanning mechanistic investigations, from cell to tissue microenvironments, on vascular mechanotransduction events and could facilitate development of mechanotherapeutics.